Efficacy of combined estrogen–progestin hormone contraception therapy for refractory coronary spastic angina in very young women. Issue 5 (May 2020) - Tezuka, Ayako; Shiina, Kazuki; Fujita, Yasuhiro; Nemoto, Yoshiko; Nakano, Hiroki; Fujii, Masatsune; Yazaki, Yoshinao; Yamashita, Jun; Sakai, Yosuke; Kuji, Naoaki; Nishi, Hirotaka; Chikamori, Taishiro
Abstract: Coronary spastic angina (CSA) in premenopausal women is rare, but has also been suggested to be associated with estrogen decline during the menstrual cycle. In this report, we describe the case of a young premenopausal patient with refractory CSA. She presented with ventricular fibrillation (VF) at the age of 15 years and was diagnosed as having CSA. She underwent implantation of an Implantable Cardioverter Defibrillator (ICD), and despite receiving systemic drug therapy at the maximum doses, she experienced a total of four appropriate ICD shocks over the subsequent six years. Based on careful history-taking, it was suspected that the angina episodes were closely related to the phase of the menstrual cycle. We started the patient on continuous combined estrogen–progestin hormone contraception therapy so as to prevent the reduction of the blood estrogen levels just prior to and during menstruation. After the start of this treatment, the patient became completely free of angina episodes. Although there are a few reports of the efficacy of hormone replacement therapy in premenopausal women with CSA, this is the first report of the efficacy of this therapy in a woman as young as 22 years old. <Learning objective: There are a few reports of episodes of CSA occurring in relation to the phase of the menstrual cycle in premenopausal women. It is considered to be associated with decline of the blood estrogen levels and combined estrogen plus progestin contraception therapy may be effective in such cases.>